North Pacific deep-sea ecosystem responses reflect post-glacial switch to pulsed export productivity, deoxygenation, and destratification. (October 2020) - Belanger, Christina L.; Sharon,; Du, Jianghui; Payne, Calie R.; Mix, Alan C.
Abstract: Deep-sea ecosystems are highly sensitive to changes in organic matter export and oxygenation driven by climate change. Here we document past ecological changes in benthic foraminiferal assemblages indicative of deglacial changes in deep-sea oxygenation and the character of organic matter fluxes from sedimentary records retrieved at intermediate (692 m) and abyssal (3667m) depths in the Gulf of Alaska. Constrained multivariate ordination combining faunal and geochemical data over the past 22, 000 years distinguishes the impacts of pulsed productivity, which exports carbon to the abyss, from extreme dysoxia across the deglacial warming transition. At both depths, opportunistic species are more prevalent in interglacial conditions, reflecting higher pulsed organic matter export to the seafloor developed in response to warming and reduced sea-ice cover. Benthic foraminiferal species tolerant of low-oxygen conditions increased in abundance during the deglacial transition at both intermediate and abyssal depths. Authigenic trace metals reveal sulfidic sedimentary conditions indicative intermittent anoxia, but only at intermediate-depths. Benthic foraminiferal richness and evenness are also highest during this deglacial low-oxygen interval, likely due to high food availability. Last Glacial Maximum faunas were distinctly different at the two sites, consistent with a more stratified deep Pacific, but the faunas become more similar during Holocene time, suggesting destratification of the abyss during deglaciation. These ecosystem responses support that carbon fluxes increased during warm intervals in subpolar regions and underscores the importance of considering the effects of transient biological blooms on paleoceanographic interpretations and in model projections of future deep carbon export. Highlights: Foraminiferal faunas in Gulf of Alaska reflect glacial-interglacial climate change. Multivariate ordination analyses separate effects of dysoxia and organic matter flux. Organic matter export is pulsed in the Holocene compared to the Glacial Maximum. Dysoxia occurred at intermediate depth and suboxia at abyssal depth in deglacial. Abundant food makes deglacial abyssal benthic foraminiferal assemblages diverse.